PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK BERKIRIM SALAM UNTUK MENINGKTKAN HASIL BELAJAS SISWA MATA PELAJARAN IPS KELAS IV DI SD NEGERI 036 SINTONG KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Elvira Yenti; Makhdalena '; Hendripides ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstack: Cooperative learning model is a model of learning with an emphasis on the social aspects of learning using small groups of 4-5 students with a heterogeneous structure of the group in achieving the learning objectives. Cooperative learning model exchanging greetings technique is one of the cooperative learning techniques, which gives the opportunity to practice the knowledge and skills of students. In addition to training the knowledge and skills of students, this technique is also expected to improve student learning outcomes. In this research aims to improve the learning outcomes of students social studies classes IV in SDN 036 Sintong district Tanah Putih district Rokan Hilir with cooperative learning model. The location of this research in SD Negeri 036 Sintong district Tanah Putih district Rokan Hilir. Samples in this study is a Class IV student of State 036 Sintong district amounting to 23 people. Data were obtained by a test sheet student learning outcomes. Data analysis techniques performed by observation of the teacher's behavior and collect data to learn the results obtained from the social studies test students and analyzed with descriptive statistical techniques. From the analysis result that after the implementation of cooperative learning model technique exchanging greetings, there is increased activity of teachers, increase the activity of students and student learning outcomes also increased. From the results of research conducted suggested that primary school teachers 036 Sintong can use cooperative learning techniques exchanging greetings as an alternative learning to improve student learning outcomes..Keywords: Cooperative Learning Model Engineering exchanging greetings , Learning Outcomes.